2018
DOI: 10.1111/sji.12666
|View full text |Cite
|
Sign up to set email alerts
|

UC‐1V150, a potent TLR7 agonist capable of activating macrophages and potentiating mAb‐mediated target cell deletion

Abstract: Toll-like receptors (TLR) are critical mediators of the immune system with their activation linked to infection, inflammation and the pathogenesis of immune diseases including autoimmunity and cancer. For this reason, over the last 2 decades, TLR and their associated signalling pathways have been targeted therapeutically to enhance innate and adaptive immunity. Several TLR ligands, both endogenous and synthetic are at various phases of clinical testing, and new ligands are continually emerging. Agonists of TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A few examples have been depicted in Figure 3. [67,68,69,70]. Furthermore, combination of TLR ligands into multivalent conjugates could lead to synergistic effects and phenotypically distinct polarisation states [71,72].…”
Section: Targeting Tumour-associated Macrophages In the Tumour Micmentioning
confidence: 99%
“…A few examples have been depicted in Figure 3. [67,68,69,70]. Furthermore, combination of TLR ligands into multivalent conjugates could lead to synergistic effects and phenotypically distinct polarisation states [71,72].…”
Section: Targeting Tumour-associated Macrophages In the Tumour Micmentioning
confidence: 99%
“…Using knowledge from the literature and considering the available antibodies for mouse targets, we stained for CD163 and Fcgr4. According to ImmGen (Figure 1, 20) and previous reports (16, 17), Fcgr4 is expressed by macrophages and neutrophils. This is corroborated by flow cytometric analysis (Figure 3G).…”
Section: Resultsmentioning
confidence: 55%
“…Applying our revised protocol to test over 35 primary antibodies specific for mouse immune subsets, we developed a panel of lymphoid and myeloid cell markers (Table 1). These markers were chosen based on ImmGEN expression data (Figure 1, 20), previous reports (16, 17, 2124), and antibody availability. Using chromagen and fluorescence (via tyramide signal amplification) detection methods, we observed that each marker produced expected staining patterns corresponding with known localization and expression by the respective cell types of interest (Supplemental Figures 4, 25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treated tumors accumulated antitumor TAMs, which killed tumor cells directly through the production of NO and were essential for the antitumor activity [ 248 ]. In addition, TLR7/8 agonists reprogramed protumoral TAMs into antitumoral effectors in mouse models of melanoma (B16) and colon cancer (MC38) [ 249 ] and TAMs become very efficient at antibody-mediated phagocytosis [ 250 , 251 ]. Thus, TLR7/8 agonists are considered valuable additional reagents with great potential in combinations with ICB and vaccination and are intensely being investigated.…”
Section: Tumor Therapies Targeting Macrophagesmentioning
confidence: 99%